Recognizing of movement samples on the basis of the kinetics by fuzzy logic by the example of different giant swings - Hansen, M. (International Journal of Computer Science in Sport, 2006)
No movement resembles the other one, however we can recognize patterns of movement for example a giant swing as such. The aim of the experiment was to examined whether a differentiation of two movement classes of giant swings on the basis of kinematic data is possible by fuzzy logic (Zadeh, 1984).